Meneliti Korelasi Antara Kekuatan Otot Hamstring dan Performa Lompatan Vertikal di Kalangan Petugas Pemadam Kebakaran - Anwari, Aulya Safiyna Nuuril; Widodo, Achmad; Sulistyarto, Soni; Firmansyah, Awang (Institut Teknologi Bandung, 2026)
Firefighting is a physically demanding occupation requiring high levels of muscular strength and power to perform tasks such as victim rescue, stair climbing, hose dragging, and equipment handling under unpredictable and hazardous conditions. This study aimed to examine the relationship between hamstring muscle strength and countermovement jump performance in firefighters. This study employed a quantitative cross-sectional design. Participants were active-duty firefighters who met the inclusion criteria. Total the participants are 43 with male gender, the body weight of 73,83 ± 10,38 kg, height of 172,44 ± 4,68 cm, Body Mass Index (BMI) was 24,79 ± 3,13 kg/m² . The results showed a significant relationship between hamstring muscle strength and countermovement jump power. The correlation between L Max Force and jump power was statistically significant (p = 0,002), as was the relationship between R Max Force and jump power (p = 0,001), both below the significance threshold of <0,05. These findings indicate that greater hamstring muscle strength is associated with higher CMJ power output. In conclusion hamstring muscle strength is significantly related to lower-limb explosive performance in firefighters.